MTMR7 regulates human spermatogonial stem cells proliferation and migration via targeting FLNB - Nianchao Zhou; Tiantian Wu; Yi Yu; Wenxin Gao; Bing Jiang; Haoyue Hu; Xiaoyan Huang; Cong Shen; Yibo Wu; Tingting Gao (PLoS ONE, 2025)
In the testes, spermatogonial stem cells (SSCs) maintain normal spermatogenesis through the dual potential of self-renewal and differentiation, which is essential for male fertility. Myotubularin-associated protein 7 (MTMR7), as a vital member of MTMR family with phosphatase activity, is involved in a variety of membrane transport processes through regulating the levels of phosphoinositides (PIPs). Our earlier research demonstrated that MTMR7 controls the cell cycle and maintains homeostasis in mouse SSCs by inhibiting PI3K/AKT signaling. However, its role in human SSCs has not been reported. This study found that knocking down MTMR7 increased the proliferation and migration of human SSCs, whereas MTMR7 overexpression inhibited these processes. Through mass spectrometry and immunoprecipitation, we identified filamin B (FLNB) as an interacting protein of MTMR7, and MTMR7 is required for FLNB ubiquitination and subsequent degradation. Further validation using immunofluorescence confirmed the involvement of the downstream β-catenin signaling. Altogether, this study is the first to demonstrate that MTMR7 regulates β-catenin expression and inhibits human SSCs proliferation and migration by mediating the ubiquitination and degradation of FLNB. These findings may offer new therapeutic strategies and target gene loci for treating male infertility caused by SSCs dysfunction.